2008
DOI: 10.1111/j.1538-7836.2007.02870.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced thrombocytopenia in patients requiring prolonged intensive care unit treatment after cardiopulmonary bypass

Abstract: patients requiring prolonged intensive care unit treatment after cardiopulmonary bypass. J Thromb Haemost 2008; 6: 428-35.Summary. Background: The diagnosis of heparin-induced thrombocytopenia (HIT) is problematic in postcardiac surgery (CS) intensive care unit (ICU) patients, as there are multiple potential explanations for thrombocytopenia and the presence of anti-platelet factor 4/heparin antibodies is not highly specific for HIT. Two platelet count profiles for HIT -a 40% or greater fall in platelet count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…These findings therefore confirm the high positive predictive value (100%) of the P1 pattern for HIT, in agreement with our previous study [9]. In a retrospective analysis performed in 329 selected cardiac surgery patients who had required prolonged intensive care treatment post-operatively, this profile of PC evolution was also previously found by Selleng et al [12] to be more frequent (12.1%).The clinical condition was severe in these patients but other potential reasons explaining this difference are not discussed in the present article. One explanation might be the different threshold values of the fall in PC (i.e.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These findings therefore confirm the high positive predictive value (100%) of the P1 pattern for HIT, in agreement with our previous study [9]. In a retrospective analysis performed in 329 selected cardiac surgery patients who had required prolonged intensive care treatment post-operatively, this profile of PC evolution was also previously found by Selleng et al [12] to be more frequent (12.1%).The clinical condition was severe in these patients but other potential reasons explaining this difference are not discussed in the present article. One explanation might be the different threshold values of the fall in PC (i.e.…”
supporting
confidence: 93%
“…The optical density that had been measured by PF4-specific immunoassay in the five patients with positive HIPA is not precisely defined in the article, although this parameter has been shown to be helpful in improving the specificity of HIT diagnosis [13]. The recommendation to continue heparin in cases of persistent post-operative thrombocytopenia despite positive results on immunoassay is important for clinical practice, but it is not supported by two previous studies (including one from Selleng et al) that reported several cardiac surgery patients with similar PC evolution who were finally judged to have developed HIT [10,12].…”
mentioning
confidence: 99%
“…The low risk of HIT that we have identified in these patients at least provides a rationale for considering continued heparin therapy in such patients, even if a PF4-heparin antibody test result is positive. Maintaining heparin should be particularly considered when there is a reasonable alternative explanation for the thrombocytopenia, there is no new thrombosis (which would increase the likelihood of ÔtrueÕ HIT), and no additional platelet count decrease of at least 30% occurs during the characteristic HIT ÔwindowÕ between days 5 and 10 [16]. Previous studies have reported lower platelet counts in anti-PF4-heparin antibody-positive patients than in those who are antibody-negative post-cardiac surgery [9,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, several features suggested that these patients probably had non-HIT thrombocytopenia associated with incidental seroconversion: (i) their platelet count course did not differ from that of the 20 HIPA-negative patients (Fig. 2); (ii) none of the HIPA-positive patients with early-onset and persisting thrombocytopenia showed an additional 30-49.9% decrease in platelet counts after day 4, which has been recently identified as a risk factor for HIT in post-cardiac surgery patients with persistent thrombocytopenia [16]; (iii) none of the five patients developed thrombosis, or died, as compared with three each who developed thrombosis, or died, among the 20 HIPA-negative patients; and (iv) four of these five patients (including the one patient with a positive HIPA result at preoperative baseline) were suspected of having HIT during the study, and switched to a non-heparin anticoagulant at day 4 (three patients) or at day 5 (the fourth patient), but in none did the platelet counts subsequently recover by day 10 (Fig. 2).…”
Section: Mean Platelet Counts and Antibody Statusmentioning
confidence: 98%
“…11,12 Furthermore, preimmunization by sepsis could not explain the presence of naturally occurring anti-PF4/heparin Abs in 3%-8% of the normal population. 6,10,13 We hypothesized that periodontitis might be a cause of preimmunization to PF4/heparin complexes.…”
Section: Introductionmentioning
confidence: 99%